Perfil da gestão e dos gestores nas escolas estaduais da região da AMOP: uma análise dos questionários contextuais da Prova Brasil - Soligo, Marinez Gasparin (2019)
This research starts from the following problem: What is the profile of school management and managers of the state network of Final Years of Elementary School of the Association of Western Paraná Municipalities – AMOP, based on the contextual questionnaires of Prova Brasil 2015? The discussion started from some aspects of the theoretical and conceptual field of the school management history. This was an important process, as relevant themes were constituted for the understanding of the role of the manager and the management in the current educational processes. With the objective of building the profile of the management and managers of state elementary schools, final years, of the municipalities that make up the region of AMOP. The analysis was performed from the questionnaire answered by the directors at Prova Brasil 2015, which are available on the website of the National Institute for Educational Studies and Research Anísio Teixeira (INEP). This research is divided into four chapters in which we present the history of school administration in Brazil, the Large-Scale evaluations, the methodology adopted in this work and the data analyzed from the 2015 Prova Brasil contextual questionnaires in the AMOP region. The resulting analysis of this study was that the profile of principals / managers of state schools are white women over 40 years old, with degrees in private institutions held for over 15 years who accessed the function through direct election. And the school management profile of the state schools in the AMOP region has the characteristics of a democratic and participatory, most of which have the School Council, the Class Council and the Pedagogical Political Project as form of management regularly carried out with the participation of the school. School community and financial distress, lack of teachers and staff and student discipline.